SUMBERDAYA MANUSIA BERKUALITAS dan BERKARAKTER - Bendesa, I Komang Gde (PIRAMIDA; Vol 10 No 1 (2014): Jurnal PIRAMIDA, 2014)
Human capital is one resource that can produce goods and services. Human capital as a multi-dimensional concept has meaning according to the interests of use. Similarly, human capital is the physical capital of the oldest in the world that is inherent in human beings that have been created since the human and born. Human capital has a narrower meaning than human resources, as more measure of the economic benefits alone. Report of the World Economic Forum includes human capital index of 122 countries in the world. However, the human capital index has not entered a real human character element is very important in improving the quality of human resources, in order to form a strong national character. In this paper, based on the character of the cultural elements included in the measurement of human resources that can be done through formal and informal education
Keywords: human capital; human resources; the character of the nation